2014
DOI: 10.1111/cei.12319
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced formation and impaired degradation of neutrophil extracellular traps in dermatomyositis and polymyositis: a potential contributor to interstitial lung disease complications

Abstract: SummaryDermatomyositis (DM) and polymyosits (PM) are systemic autoimmune diseases whose pathogeneses remain unclear. Neutrophil extracellular traps (NETs) are reputed to play an important role in the pathogenesis of autoimmune diseases. This study tests the hypothesis that NETs may be pathogenic in DM/PM. Plasma samples from 97 DM/PM patients (72 DM, 25 PM) and 54 healthy controls were tested for the capacities to induce and degrade NETs. Plasma DNase I activity was tested to further explore possible reasons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 29 publications
(67 reference statements)
5
74
0
3
Order By: Relevance
“…Plasma cfDNA and LL-37 could be used as biomarkers for NET formation in vivo [4]. We compared plasma cfDNA and LL-37 in the different study groups and found that both were significantly increased in DM patients, especially in DM patients with ILD ( Figure 3A, B, D, and E), which indirectly indicates that NET formation is enhanced in DM patients with ILD.…”
Section: Neutrophil/net-related Markers Were Significantly Increased mentioning
confidence: 87%
See 1 more Smart Citation
“…Plasma cfDNA and LL-37 could be used as biomarkers for NET formation in vivo [4]. We compared plasma cfDNA and LL-37 in the different study groups and found that both were significantly increased in DM patients, especially in DM patients with ILD ( Figure 3A, B, D, and E), which indirectly indicates that NET formation is enhanced in DM patients with ILD.…”
Section: Neutrophil/net-related Markers Were Significantly Increased mentioning
confidence: 87%
“…In our previous study, we established that the formation of neutrophil extracellular traps (NETs) was enhanced and these increased NETs could not be completely degraded in vitro, which was associated with ILD in DM patients [4]. Activated by microbes, neutrophils can trap and kill invading microbes by releasing DNA, histones, and antimicrobial peptides to form NETs [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Zhang et al demonstrated that serum from patients with Jo-1 antibodies and/or subacute ILD promoted the in vitro development of NETs through enhanced formation as well as impaired DNAse I-mediated degradation [25]. Correlating with these in vitro studies, serum derived from patients with Jo-1 antibodies demonstrated higher levels of LL-37 and cell-free DNA [25]-both of which are markers of in vivo NET formation.…”
Section: Hrs (Jo-1) Possesses (In Vitro) Chemokine Properties-acts VImentioning
confidence: 95%
“…In a recent study, Zhang et al demonstrated that serum from patients with Jo-1 antibodies and/or subacute ILD promoted the in vitro development of NETs through enhanced formation as well as impaired DNAse I-mediated degradation [25]. Correlating with these in vitro studies, serum derived from patients with Jo-1 antibodies demonstrated higher levels of LL-37 and cell-free DNA [25]-both of which are markers of in vivo NET formation. Because NETs are comprised of proteases and other proteins capable of damaging endothelial/ epithelial components of various tissues, this mechanism provides a link between pro-inflammatory cytokine cascades, dysregulated formation/clearance of NETs, aberrant antigen exposure (e.g., HRS), autoreactivity, and specific organ manifestations such as ILD.…”
Section: Hrs (Jo-1) Possesses (In Vitro) Chemokine Properties-acts VImentioning
confidence: 95%
“…Similarly, a very recent study indicated the key role of neutrophil elastase in the promotion of myofibroblast differentiation in experimental lung fibrosis, confirming indirectly but clearly the significance of NETs and their decorative components in fibrotic process [16]. Furthermore, at the same time when the critical role of NETs in inflammation-driven fibrosis was revealed [9], an independent clinical study demonstrated that decreased DNase I activity in dermatomyositis/polymyositis patients is significantly associated with interstitial lung disease, linking the abnormal clearance of NETs with a well-defined, severe fibrotic complication [17]. Considering that the lifespan of neutrophils is very short, and in many fibrotic cases the biopsies are performed when the fibrosis is established, it is rational to explain why neutrophils cannot be visualized in fibrotic tissues by conventional methods used in everyday pathology practice (e.g.…”
Section: Introductionmentioning
confidence: 72%